Strategic leadership theory and research on executives, top management teams, and boards - Finkelstein, Sydney (New York Oxford University Press, 2009)
This book integrates and assesses the vast and rapidly growing literature on strategic leadership, which is the study of top executives and their effects on organizations. The basic premise is that in order to understand why organizations do the things they do, or perform the way they do, we need to deeply comprehend the people at the top-- their experiences, abilities, values, social connections, aspirations, and other human features. The actions--or inactions--of a relatively small number of key people at the apex of an organization can dramatically affect organizational outcomes.
Includes bibliographical references (p. 383-450) and index.
Keywords: Leadership